The Hungarian labour market 2014 - Institute of Economics of Hungarian Academy of Sciences, Budapest (Budapest, 2014)
"The Hungarian Labour Market Yearbook series was launched 14 years ago by the Institute of Economics of the Hungarian Academy of Science with support from the National Employment Foundation (OFA). The yearbook presents the main characteristics of Hungarian employment policy and each year features an in-depth analysis of a topical issue. The current volume examines the characteristics of public sector employment. From the outset, the editorial board has striven to bring relevant and usable information on trends in the Hungarian labour market, the legislative and institutional background of employment policy, and up-to-date findings from Hungarian and international research to policy makers, civil servants, government officials, higher education and research institutions, and the press and electronic media. The research published in the yearbook series would also provide a good source of knowledge for higher education on the topics of labour economics and human resources management. The yearbook presents the main characteristics and trends of the Hungarian labour market in an international comparison using available statistical information, conceptual research and empirical analysis in a clearly structured and easily accessible format."